2014
DOI: 10.1093/ajh/hpu229
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Biomarkers of Renal Function With Cerebral Microbleeds in Hypertensive Patients

Abstract: Kidney biomarker levels are associated with the presence of CMB in hypertensive patients without a history of transient ischemic attack (TIA) or stroke, independent of conventional risk factors, and CysC was a better marker for CMBs than eGFR and UACR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…In particular, the Brain in Kidney Disease study evaluated 240 subjects with CKD and controls and reported that a 10% increment in ACR was independently associated with an increase of 0.24% in WMH volume, but no association with CMBs was documented. A cross‐sectional study of 568 individuals with hypertension without a history of stroke found that 1 SD increase in ACR was associated with higher odds for deep and infratentorial CMBs (OR = 2.03, 95% CI = 1.41–4.31), but no association was found for lobar CMBs . A population‐based study found an association between baseline ACR and WMH volume after 7 years ( β = 0.039, P = .05) and a stronger association when ACR and WMH were concurrently assessed ( β = 0.073, P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the Brain in Kidney Disease study evaluated 240 subjects with CKD and controls and reported that a 10% increment in ACR was independently associated with an increase of 0.24% in WMH volume, but no association with CMBs was documented. A cross‐sectional study of 568 individuals with hypertension without a history of stroke found that 1 SD increase in ACR was associated with higher odds for deep and infratentorial CMBs (OR = 2.03, 95% CI = 1.41–4.31), but no association was found for lobar CMBs . A population‐based study found an association between baseline ACR and WMH volume after 7 years ( β = 0.039, P = .05) and a stronger association when ACR and WMH were concurrently assessed ( β = 0.073, P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Previously, several studies linked chronic kidney disease in (pre)dialysis patients to the presence of CMBs, and in several cross-sectional studies in stroke patients, hypertensive patients and in the general population, impaired kidney function was associated with the presence of CMBs. [3][4][5][6][7][8][9][10][11][12][13] Thus far, there are no longitudinal data on the relation between decreased kidney function and progression of CMBs. To strengthen the association between both small vessel pathologies, we performed a longitudinal study to determine if decreased kidney function was related to CMBs progression after two years of follow-up in lacunar stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the presence of CMBs is considered a risk factor for both intracranial hemorrhage and ischemic stroke in healthy elderly populations and was identified as an independent risk factor in a population of patients with intracranial hemorrhage . In people, risk factors for CMBs include CAA, hypertension, renal disease, proteinuria, and pro‐inflammatory states …”
mentioning
confidence: 99%
“…12,13 Additionally, the presence of CMBs is considered a risk factor for both intracranial hemorrhage and ischemic stroke in healthy elderly populations 14 and was identified as an independent risk factor in a population of patients with intracranial hemorrhage. 15 In people, risk factors for CMBs include CAA, hypertension, 8 renal disease, [16][17][18] proteinuria, 19 and pro-inflammatory states. 20 Pathological changes seen in humans with CAA have been recognized in older dogs, 21,22 although these lesions have not been identified as resulting in neurologic deficits in veterinary medicine.…”
mentioning
confidence: 99%